Simulation, Fabrication And Characterization Of Multilayer Coated Solar Cells - Aziz, Wisam J. (2011)

(untitled)
This work is a combination of a theoretical simulation and an experimental fabrication of multilayer coated solar cells. ISE-TCAD simulator, release 9.5 was used in the theoretical part. A simulation model was established by employing known theories relevant to solar cells and the experimental data was applied to validate the simulation results.The solar cells were fabricated by means of texturing and antireflection coating. For texturing, alkaline (KOH) and mixture acidic solution (HNO3+HF+CH3COOH, 15:3:2) were used. For antireflection coating, ZnO/TiO2 and porous silicon were used to increase the light trapping of solar cell structures.